Canada–Indonesia relations, past and present. (September 2019) - Webster, David
Canada–Indonesia relations recently passed their 65th anniversary, but they still have a tentative air about them. Despite regular talk about developing a strong Canadian relationship with a country that potentially has much in common with Canada, Canada–Indonesia relations have mostly been friendly but shallow. An overview of the history of bilateral relations, from the opening of a Canadian mission in 1953 to recent bilateral deals committing Ottawa and Jakarta to various forms of collaboration, reveals that rhetoric about common interests has some substance, but a new announcement amidst good intentions every few years is not likely to lead to any deep partnership. There are, however, foundations for closer ties in civil society, including in the fields of economic development, truth and reconciliation, religious deradicalization, and Indigenous peoples linkages.